Mechanical, thermal, viscoelastic and hydrophobicity behavior of complex grape stalk lignin and bamboo fiber reinforced polyester composite - Alshahrani, Hassan; Arun Prakash, V.R. (International journal of biological macromolecules, 2022)
This work aims to investigate the degradation stability of bamboo fiber-reinforced polyester composite toughened with complex lignin biopolymer derived from the waste grape stalks. The properties like mechanical, wear, thermal, DMA, and hydrophobic were studied after the addition of lignin and analyzed how the lignin addition influenced these properties. Prior to composite making the fiber and lignin was treated with silane. According to the results obtained incorporating 40 vol% of bamboo fiber into the polyester resin, the mechanical and wear properties enhanced. Further, the composite containing 2.0 vol% of lignin has maximum tensile strength, tensile modulus, flexural strength, flexural modulus, and ILSS. Similarly, the composite designation having 4 vol% lignin revealed the improved wear loss stability of 0.007 mm3/Nm (sp. wear rate). The highest degradation temperature reported for composite designation UBL4 it was 520 °C, with a relatively lesser weight loss of 19 %. Likewise, the highest storage modulus was about 4.5 GPa, and the lowest loss factor was up to 0.3 for the composite designation UBL4. The contact angle investigation revealed that all composite designations are not fall below 70°, indicating their hydrophobic stability. These composites with enhanced stability against load, heat and water could be utilized in the industrial, automotive and defense sectors where high performance outcomes are required.